“TEEN ISLAM” The Rise of Teenagers-Segmented Islamic Transmission through Popular Media in Indonesia (State Islamic University (UIN) of Sunan Ampel Surabaya, 2010)
Religious-cum-cultural studies have lately noted the increasing concern of people with the religious life of the young and the teenagers. The production and consumption of Islam for teenagers have been widely undertaken. The publications, both print and non-print, have become evidence of this increasingly wide production and consumption of Islam for teenagers. Much has been written for examining this production and consumption of Islam. But, less has been devoted to analysing the growing production of Islam segmented for Muslim teenagers, particularly in relation to the historical context of the rise of this teenagers-segmented Islam, genres of this teenagers-segmented Islamic print publication, and the way of presenting Islamic ideas. This paper focuses on the rise of Islamic teen literature along with its different genres in a current context of Indonesia. In doing so, it is particularly concerned with the examination of the production of Islamic ideas among those Muslim teenagers through such a kind of print publication.